TAHAP PEMBUKTIAN DI DALAM KES-KES JENAYAH: KAJIAN PERBANDINGAN ANTARA UNDANG-UNDANG ISLAM DAN SIVIL - Md Hashim, Ashraf (Jurnal Syariah, 2019)
The existence of a just judiciary system is very importance to ensure justice, peace and harmony in a country. One of its principles is related to a burden of proof in order to protect the public from wrongdoing of criminals and at meantime to protect the accused of being sentenced without proper trial. In terms of burden of proof is concerned, this article tries to make a comparison between Islamic criminal law and conventional ones. In short, both systems have different degrees of proof either in criminal cases or civil. It is discussed here cases particularly related to qisiis, hudiid and ta’zlr in Islam. It is found that there are similarities in terms of burden of proof between the two. However, there are also differences. Therefore, this article attempts to analyze and criticize these differences and to suggest which one is the best to be applied in the court in order to do justice both to the accused and the victims.